Uang Perspektif Al-Qur'an Dan Hadits - Fahrurrozi (Revenue : Jurnal Ekonomi Pembangunan dan Ekonomi Islam, 2020)
Money in conventional economics is defined as any medium of exchange that is generally accepted. The exchange tool is in the form of objects that can be accepted by everyone in the community in the process of exchanging goods and services. In Islamic economics, the etymology of money comes from the word al-naqdu, meaning there are several meanings: al-naqdu means good from dirham, holds dirham, distinguishes dirham, and al-naqdu also means cash. The word nuqud does not exist in al-quran and hadith, because Arabs generally do not use nuqud to show prices. They used the word dinar to denote a currency made of gold and the word dirham to indicate a medium of exchange made of silver. They also used wariq to show silver dirhams, said 'ain to denote gold dinars.